Collaboration orchestration in complex rehabilitation services—a qualitative study. - Skumsnes, Randi; Thygesen, Hilde; Groven, Karen Synne (Journal of Interprofessional Care)
Interprofessional collaboration in rehabilitation is essential but challenging. Although factors supporting interprofessional collaboration are well known, how professionals make collaboration work within complex practices is underexamined. In response, we explored interprofessional collaboration and communication in a complex, dynamic rehabilitation setting, along with how healthcare professionals experience such collaboration and their actions to make it work across organizational boundaries. To those ends, we conducted semi-structured individual interviews with 14 healthcare practitioners from a hospital and the primary healthcare rehabilitation services in Western Norway. The interview transcripts were analyzed through thematic analysis, and we applied the theoretical perspective of relational expertise in interpreting the findings. We developed two main themes with sub-themes: that professionals enable and orchestrate collaborative work by (1) using different communication approaches flexibly and adjusting the collaboration to each patient's needs and to the collaborative situation, and (2) acknowledging the significance of interpersonal relations by cultivating mutual trust and understanding. Those new insights contribute to interprofessional practice by urging practice and policymakers to acknowledge practitioners' need for flexibility and to develop relational expertise as well professional expertise, especially in dynamic rehabilitation settings. Practitioners, educators and policymakers should support the cultivation of collaborative skills and structures.